Total flavonoids of hawthorn leaves protect spinal motor neurons via promotion of autophagy after spinal cord injury - Qiong Zhang; Mingfu Liu; Haibin Nong; Yanan Zhang; Yiguang Bai; Pan Liu; Shaohui Zong; Shaohui Zong; Gaofeng Zeng (Frontiers in Pharmacology, 2022)
The death of spinal motor neurons (SMNs) after spinal cord injury (SCI) is a crucial cause, contributing to a permanent neurological deficit. Total flavonoids of hawthorn leaves (TFHL) have been confirmed to have potentially therapeutic for SCI. Nonetheless, the roles and mechanisms of TFHL in recovering neuromotor function and regenerating axons of SMNs have not been fully elucidated. In this study, TFHL was applied to treat rats with SCI and injured SMNs for 7 days. In vivo experiment, rats with SCI were evaluated by a BBB (Basso-Beattie-Bresnahan) score to assess their motor functional recovery. The morphology, microstructure, apoptosis, Nissl bodies, and autophagy of SMNs in spinal cord tissue were detected by Hematoxylin-eosin (HE) staining, transmission electron microscopy, TUNEL staining, Nissl staining, and immunohistochemistry respectively. In vitro experiment, the co-culture model of SMNs and astrocytes was constructed to simulate the internal environment around SMNs in the spinal cord tissue. The cell morphology, microstructure, axonal regeneration, and autophagy were observed via optical microscope, transmission electron microscopy, and immunofluorescence. The content of neurotrophic factors in the cell culture medium of the co-culture model was detected by ELISA. Moreover, the expression of axon-related and autophagy-related proteins in the spinal cord tissue and SMNs was measured by Western Blot. We demonstrated that TFHL improved the neuromotor function recovery in rats after SCI. We then found that TFHL significantly promoted injured spinal cord tissue repair, reduced apoptosis, and improved the functional status of neurons in spinal cord tissue in vivo. Meanwhile, the cell morphology, microstructure, and axonal regeneration of damaged SMNs also obviously were improved, and the secretion of neurotrophic factors was facilitated after treatment with TFHL in vitro. Further, we revealed that TFHL promoted autophagy and related protein expression in vivo and vitro. Taken together, our study suggested that TFHL might facilitate autophagy and have neuroprotective properties in SMNs to enhance the recovery of neuromotor function of rats with SCI.